2006
DOI: 10.1242/jeb.02322
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of rapid vertical climbing in cockroaches reveals a template

Abstract: . Single-leg force patterns differed significantly from level running. During vertical climbing, all legs generated forces to pull the animal up the plate. Front and middle legs pulled laterally toward the midline. Front legs pulled the head toward the wall, while hind legs pushed the abdomen away. These singleleg force patterns summed to generate dynamics of the whole animal in the frontal plane such that the center of mass cyclically accelerated up the wall in synchrony with cyclical side-to-side motion that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
246
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 194 publications
(254 citation statements)
references
References 63 publications
6
246
2
Order By: Relevance
“…However, their prediction only addresses perpendicular (pulloff) forces. Animals climbing vertically load their adhesives primarily in the shear direction (15,39), for which few, if any, models currently exist to generate scaling predictions in either dry or wet fibrillar adhesives. Although several independent hypotheses lead to a contact splitting prediction, we question the assumption that biological data must necessarily confirm it, or any other still untested models of fibrillar adhesion (1).…”
Section: Resultsmentioning
confidence: 99%
“…However, their prediction only addresses perpendicular (pulloff) forces. Animals climbing vertically load their adhesives primarily in the shear direction (15,39), for which few, if any, models currently exist to generate scaling predictions in either dry or wet fibrillar adhesives. Although several independent hypotheses lead to a contact splitting prediction, we question the assumption that biological data must necessarily confirm it, or any other still untested models of fibrillar adhesion (1).…”
Section: Resultsmentioning
confidence: 99%
“…We proposed more broadly that the appropriate modulation of the two waves was in fact a control "template," defined as a behavior that contains the smallest number of variables and parameters that exhibits a behavior of interest (12). Templates provide relatively simple targets for motion control and feedback responses (13) and have proved useful to understand locomotion of legged runners (14), climbers (15), and undulatory swimmers (16).…”
Section: Significancementioning
confidence: 99%
“…Cockroaches use rigid, jointed exoskeletons to run rapidly at speeds approaching 1.5 m·s −1 (31), climb up walls (11,32), race along ceilings (33), and swing stealthily under ledges out of sight (34). However, materials science has revealed that the stiffness of exoskeletal tissue can differ by eight orders of magnitude (35)(36)(37)(38), permitting the possibility that cockroaches with powerful propulsive appendages might also retain the advantages of soft-bodied animals capable of conforming to their environment (39).…”
mentioning
confidence: 99%